Efektivitas Penerapan Pelayanan Program Perizinan Berusaha Berbasis Online Single Submission (OSS) di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) - Gunawan, Celsea Yasmin Febryna; Purnamaningsih, Putu Eka; Winaya, I Ketut (Business and Investment Review, 2023)
Licensing is one of the most important components for running a business in each region.  The licensing process itself has been carried out online since the enactment of PP No. 24 of 2018 concerning electronically integrated business licensing or Online Single Submission (OSS).  The establishment of the OSS system aims to make it easier for the business community to apply for permits.  Indicators of effectiveness based on Cambell J P's theory are: Program Success, Target Success, Program Satisfaction, Input and Output Levels, Overall Goal Achievement.  The method used is qualitative with a descriptive approach.  Data collection was carried out by interviews, observation, documentation of the selection of informants deliberately chosen by researchers in order to obtain data, information and facts in the field accurately.  Data analysis techniques through data reduction, data presentation, drawing conclusions.  Based on the research results from interviews and observation data for each indicator, it can be said that the effectiveness of the OSS system at DPMPTSP Badung Regency is still not optimal due to several obstacles.  This is because the website still has frequent errors, there are still many business people who still don't understand technology, the community is still not very familiar with the OSS program, and there is still no online consultation service.  Recommendations that can be given are conducting socialization regularly and consistently, providing online consulting services to people who need assistance, and also improving public service technology so that people are more accustomed to using technology.